THE WEAKNESS OF THE CONTROL SYSTEM FOR FIGHTING CORRUPTION IN THE JUDICIAL PROCESS: THE CASE OF INDONESIA - Elisabeth Sundari; Anny Retnowati (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Several supervisory bodies have been established under government policy in Indonesia to prevent and eradicate corruption within the judicial process. However, these appear to be ineffective, as evidenced by the fact that corruption by judges, prosecutors, and court officials remain high [11, 12, 19, 20]. The purpose of this research is explaining the weaknesses of the control model in fighting corruption within the judicial process and its factors. Normative research has been conducted on the legal policies affecting the control system of the judicial process in Indonesia to redress the issue. The results show that from the quantitative perspective, adequate supervisory bodies have been established to deal with corruption. For instance, there is an internal supervisory body for each institution in the judicial process, together with external supervisory bodies such as the Judicial Commission, Corruption Eradication Commission, and Examination Commission. Nevertheless, from the qualitative perspective, many weaknesses remain. Firstly, government policy focuses on the model for internal supervisory bodies rather than external. Secondly, although external supervisory bodies are established, they have no broader authority, except the Corruption Eradication Commission. Thirdly, external control through community participation has limited jurisdiction. Finally, the punishment enforcement system is ineffective